USAHA PENINGKATAN PRODUKSI PADI FUNGSIONAL MELALUI APLIKASI TEKNOLOGI TEPAT GUNA DI DESA KATENG KABUPATEN LOMBOK TENGAH - Ni wayan sri Suliartini; I Ketut Ngawit; Nihla Farida (Jurnal Abdi Insani, 2022)
The limitations of irrigation facilities force farmers to cultivate the land in a hurry to get enough water, as a result, the soil puddling process is not perfect, the potential of the soil as a seed bank is high, resulting in weed problems that are difficult to control. Farmers plant seeds available in the market without tracing the origin of the seeds, varieties and quality of seeds. As a result, the productivity of rice farming in the target area is decreasing. The goal to be achieved is the transfer of appropriate technology so that the knowledge and skills of farmers about agribusiness and integrated pest management (IPM) in the cultivation of brown rice plants increase. The activity was carried out in Kateng Village, Kec. West Praya Kab. Central Lombok from January to July 2020. The method of activity carried out is the Participatory Action Program. The approach is bottom-up and top-down approach with an emphasis on the level of knowledge, skills and local wisdom of partner farmers (Hutwan et al., 2016). The implementation mechanism goes through several stages, namely counseling, determining target farmers as partners, mentoring and monitoring and evaluating programs. The results of the activity showed that the knowledge and skills of farmers about agribusiness and IPM in the cultivation of brown rice plants increased. This can be seen from the enthusiasm of the target farmers in participating in counseling and mentoring activities, as well as the application of appropriate technology, including soil processing, the use of superior seeds, organic fertilizers and IPM in rice cultivation. Appropriate technology introduced led to better growth and yield of brown rice, the intensity of planthopper attacks decreased, thus providing higher yields and benefits compared to manual cultivation.